Plumeria: Propagation from Cuttings - Andrew K. Koeser; Gitta Hasing; Drew McLean (EDIS)
Plumeria are flowering ornamentals native to the Caribbean, Mexico, Central America, Venezuela, and Colombia. Highly valued for their colorful flowers, plumeria are now grown in tropical and subtropical areas throughout the world. Plumeria, or frangipani, are members of the Apocynaceae family. Unless steps are taken to prevent frost damage, plumeria are generally limited to landscape uses in south Florida and protected regions of central Florida. This 5-page fact sheet was written by Andrew K. Koeser, Gitta Hasing, and Drew McLean, and published by the UF Department of Environmental Horticulture, October 2013.